Chemical degradation kinetics of fibrates: bezafibrate, ciprofibrate and fenofibrate - Marcelo Antonio de Oliveira; Gerliane Damázio da Silva; Michele Soares Tacchi Campos
ABSTRACT Fibrates are drugs used for the treatment of hypertriglyceridemia and for the prevention of atherosclerosis. Three drugs in the fibrate class, ciprofibrate, fenofibrate and bezafibrate, were chosen for this study because their raw materials are readily available and because scientific publications on these compounds is limited. To evaluate their intrinsic stability, the drugs were exposed to a test condition (temperature, oxidation, UV light exposure, hydrolysis at different pH values and metal ions in solution) and then were subjected to analysis by HPLC. The samples were run on a C18 column, with a flow rate of 1.0 mL min-1 in a mobile phase consisting of methanol: 0.01 % phosphoric acid v/v (80:20), with variable detection wavelengths in the UV spectra. The analysis methodology showed satisfactory performance parameters. The three drugs were very unstable, degrading in each of the conditions evaluated. The test conditions of acid and basic hydrolysis showed the most significant degradation. The results demonstrated that the drugs in this class are unstable. Based on these experimentally determined degradation kinetics, it is easy to understand and emphasize the importance of the lack of liquid dosage forms on the market for fibrates because of their instability.